Oral Vaccination With Recombinant Pichia pastoris Expressing Iridovirus Major Capsid Protein Elicits Protective Immunity in Largemouth Bass (Micropterus salmoides) - Yao, Jia-Yun; Zhang, Cheng-Sai; Yuan, Xue-Mei; Huang, Lei; Hu, Da-Yan; Yu, Zhe; Yin, Wen-Lin; Lin, Ling-Yun; Pan, Xiao-Yi; Yang, Gui-lian; Wang, Chun-Feng; Shen, Jin-Yu; et al. (Frontiers in Immunology, 2022)
Largemouth bass iridovirus (LMBV), can cause lethal and epidemic diseases in the cultivation of Micropterus salmoides. However, there is no effective treatment to control LMBV infection. Here, the present study constructed a recombinant Pichia pastoris expressing the LMBV major capsid protein (MCPD). The recombinant P. pastoris were then used to immunize M. salmoides. via oral administration, mucosal immune response mediated by Igs were measured after oral immunization. Serum antibodies level were measured by ELISA, neutralizing antibody titres were determined by SNT, antigen presentation relates genes expression were detected by RT-PCR. Immunized fish were than challenged with a lethal dose of infectious LMBV. The cumulative mortality and relative percentage survival (RPS) as well as the histopathological characteristics of immunized fish were assessed. Our results showed that the antibody level of the immunized fish was statistically significant (P < 0.05) higher than that of control groups. M. salmoides orally immunized with GS115- pW317-MCPD had high serum antibody titers that ranged from 4 to 64 after immunization and reached a peak of 1:64 on dpi 28. Ig T and Ig M expressions in gut were increased significantly after vaccination with GS115- pW317-MCPD, however much stronger response in gut was observed as compared with gill. Compared with non-vaccinated fish, the antigen processing and presentation related genes, MHC II , CD8, and TCR were elevated significantly (P<0.05), while CD4 and MHC I transcription levels remained unchanged after oral immunization (P>0.05). The results from challenge tests showed that the RPS of fish orally immunized with 1.0×108 CFU/g GS115- pW317-MCPD was reached up to 41.6 % after challenge with 0.ml 109.46TCID50/ml LMBV. Moreover, recombinant P. pastoris can significantly relieve pathological damage in liver, spleen and kidney. Therefore, GS115- pW317-MCPD could become a promising oral vaccine candidate against LMBV.